2019
DOI: 10.15252/embj.2018100368
|View full text |Cite
|
Sign up to set email alerts
|

Slx5/Slx8‐dependent ubiquitin hotspots on chromatin contribute to stress tolerance

Abstract: Chromatin is a highly regulated environment, and protein association with chromatin is often controlled by post‐translational modifications and the corresponding enzymatic machinery. Specifically, SUMO ‐targeted ubiquitin ligases ( STU bLs) have emerged as key players in nuclear quality control, genome maintenance, and transcription. However, how STU bLs select specific substrates among myriads of SUMO ylated proteins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…SUMOylated Rpb1 might serve as a recruiting factor for the STUbL Slx5-Slx8, but then target RNAPII subunits other than Rpb1 would become ubiquitylated, potentially explaining why no STUbL-dependent ubiquitylation was detected for Rpb1. STUbL-dependent ubiquitylation of proteins that are in complex with the SUMOylated STUbL-recruitment factor have been suggested in other cases and importantly for RNAPIII 55,59,60 giving precedence for this model. In contrast, previous work has shown that specifically Rpb1, but not other subunits become destabilized upon UV treatment 61 .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…SUMOylated Rpb1 might serve as a recruiting factor for the STUbL Slx5-Slx8, but then target RNAPII subunits other than Rpb1 would become ubiquitylated, potentially explaining why no STUbL-dependent ubiquitylation was detected for Rpb1. STUbL-dependent ubiquitylation of proteins that are in complex with the SUMOylated STUbL-recruitment factor have been suggested in other cases and importantly for RNAPIII 55,59,60 giving precedence for this model. In contrast, previous work has shown that specifically Rpb1, but not other subunits become destabilized upon UV treatment 61 .…”
Section: Resultsmentioning
confidence: 97%
“…Such a sequential mechanism allows the opportunity to differentially recruit proteins containing ubiquitin-and/or SUMO-interacting motifs. For instance, Cdc48 together with its co-factor Ufd1 were shown to target both ubiquitylated and SUMOylated proteins and, strikingly, also STUbL substrates 46,60,74 . SUMOylation of stalled RNAPII might therefore be a first line of defense and help in recruiting repair factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best characterized STUbLs are the yeast Slx5/Slx8 heterodimer and the mammalian RNF4 and RNF111. A recent study showed that yeast Slx5 and Slx8 are enriched at seven genomic loci termed “ubiquitin hotspots” [ 101 ]. Slx5/Slx8 are recruited to the ubiquitin hotspots by the sumoylated transcription factor-like protein Euc1, which is specifically bound to the sequence motif within these sites [ 101 ].…”
Section: Sumo-targeted Ubiquitin Ligases (Stubls) In Nuclear Protementioning
confidence: 99%
“…A recent study showed that yeast Slx5 and Slx8 are enriched at seven genomic loci termed “ubiquitin hotspots” [ 101 ]. Slx5/Slx8 are recruited to the ubiquitin hotspots by the sumoylated transcription factor-like protein Euc1, which is specifically bound to the sequence motif within these sites [ 101 ]. Ubiquitin signal at these loci was dependent on Slx5/Slx8, and was enriched in a cdc48 -mutant, indicating that Cdc48-complex is required to remove ubiquitinated proteins from the ubiquitin hotspots.…”
Section: Sumo-targeted Ubiquitin Ligases (Stubls) In Nuclear Protementioning
confidence: 99%